Credit and microfinance needs in inland capture fisheries development and conservation in Asia - Tietze, Uwe...[et al.] (FAO RomeIT, 2007)
Highlights the need to conserve and manage inland fisheries and to identify opportunities for inland fisheries development, conservation and financing. Elaborates on lending policies and procedures suitable for financing. Contains reports of the proceedings and recommendations of two regional workshops, from which the guidelines evolved. Includes case studies and success stories.